Mapping of functional regions on the transferrin-binding protein (TfbA) of Actinobacillus pleuropneumoniae. - Strutzberg, K (1995)
Actinobacillus pleuropneumoniae can use porcine transferrin as the sole source of iron. Two proteins with molecular masses of approximately 60 kDa (TfbA) and 110 kDa have been shown to specifically bind porcine transferrin; from the TfbA protein, three isoforms from A. pleuropneumoniae serotypes 1, 5, and 7 have been identified and characterized by nucleotide sequence analysis. Here we defined the transferrin-binding region(s) of the TfbA protein of A. pleuropneumoniae serotype 7 by TnphoA mutagenesis, random mutagenesis, and peptide spot synthesis. The amino-terminal half of the TfbA molecule, which has only 36% amino acid sequence identity among the three isoforms, was shown to be responsible for transferrin binding by TnphoA mutagenesis. This result was confirmed by analysis of six random mutants with decreased transferrin binding affinity. The subsequent analysis of overlapping 16-mer peptides comprising the amino-terminal half of the TfbA molecule revealed three domains of 13 or 14 amino acids in length with transferrin-binding activity. They overlapped, or were very close to, point mutations decreasing transferrin-binding ability. The first and third domains were unique to the TfbA protein of A. pleuropneumoniae serotype 7. In contrast, the sequence of the second domain was present in almost identical forms (12 of 14 residues) in the TfbA proteins of A. pleuropneumoniae serotypes 1 and 5; in addition, a sequence consisting of functionally homologous amino acids was present in the otherwise completely distinct small transferrin-binding proteins of Neisseria gonorrhoeae (TbpB), N. meningitidis (Tbp2), and Haemophilus influenzae (Tbp2).